Never Ending Brotherhood? Seeking Peace Solutions of Indonesia â Malaysia Confrontation, 1963-1966 - Sunarti, Linda (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: Confrontation events, that occurred in 1963-1966, between Indonesia against Malaysia, were a unique event. This is because the conflict at that time differs from the prevalence of conflict or war between states in general. The focus of this study is to examine the relationship between Indonesia-Malaysia during the confrontation era, 1963-1966. The main focus is the process of resolving the confrontation. This research is a qualitative study by using historical methods and structurist approaches. The resolved of conflict between the two countries was interesting, because the conflict also involved forces outside, such as Britain and the USA (United States of America), can be resolved in a short time rather than through formal meetings, but can be resolved amicably, preceded by a number of secret meetings of both parties involved directly, without going through the mediator. The results concluded that there are two factors that pushed the end of confrontation, namely: separation of Singapore from the Federation of Malaysia in August 1965 and the 30 September 1965 movement in Indonesia. Both of these events can be said to be intertwined and become the main factor of change in the attitude of the two countries related confrontation. In addition, conflict resolution can occur due to the emergence of actors in both countries with a view to the equation could change things, which have been inhibiting and destabilizing both countries and the region as well. Another important thing is secret meetings established early in the settlement process confrontation by utilizing a network of friends and fraternity. KEY WORDS: Brotherhood; Confrontation; Indonesia and Malaysia; British and USA; Peace Solutions.About the Author: Dr. Linda Sunarti is a Senior Lecturer at the Department of History, Faculty of Humanities UI (University of Indonesia), UI Campus Depok, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: lindsayrani@yahoo.co.ukHow to cite this article? Sunarti, Linda. (2017). âNever Ending Brotherhood? Seeking Peace Solutions of Indonesia â Malaysia Confrontation, 1963-1966â in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.229-242. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (August 17, 2016); Revised (December 27, 2016); and Published (April 28, 2017).